2015
DOI: 10.1093/ecco-jcc/jjv196
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced Ultrasound for Detection of Crohn’s Disease Activity: Systematic Review and Meta-analysis

Abstract: CEUS presents good sensitivity and moderate specificity in the detection of the aCD. Large-scale randomized trials with quantitative evaluation of CEUS images are necessary to promote this technique in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 46 publications
0
46
2
1
Order By: Relevance
“…CEUS can also be used to assess postoperative recurrence of Crohn's disease [199]. Two meta-analyses concluded that CEUS in the assessment of IBD activity is accurate and a highly sensitive and specific method [200,201].…”
Section: Inflammatory Bowel Disease (Ibd)mentioning
confidence: 99%
“…CEUS can also be used to assess postoperative recurrence of Crohn's disease [199]. Two meta-analyses concluded that CEUS in the assessment of IBD activity is accurate and a highly sensitive and specific method [200,201].…”
Section: Inflammatory Bowel Disease (Ibd)mentioning
confidence: 99%
“…Pallotta et al [19] demonstrated improved sensitivity (96-100% vs. 75-76%) while maintaining 100% specificity of small intestinal contrast US compared to conventional transabdominal US. Few studies have been conducted on the use of contrast-enhanced US for Crohn disease, of which both adult and pediatric populations were included [23,24]. A metaanalysis demonstrated pooled sensitivity of 94% (95% CI: 87-97%) and pooled specificity of 79% (95% CI: 67-88%) [24].…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have been conducted on the use of contrast-enhanced US for Crohn disease, of which both adult and pediatric populations were included [23,24]. A metaanalysis demonstrated pooled sensitivity of 94% (95% CI: 87-97%) and pooled specificity of 79% (95% CI: 67-88%) [24]. This technique allows for improved detection and analysis of bowel perfusion and may prove to increase US accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Also, it is effective in distinguishing inflammatory from fibrostenotic lesions, so it can provide prognostic information and guide further management [78,79]. However, its importance regarding IBD is still unclear, and more research is needed [80,81].…”
Section: Monitoringmentioning
confidence: 99%